ҚОЛАЙСЫЗ ФАКТОРЛАРҒА ОРГАНИЗМНИҢ ШЫДАМЛЫЛЫҒЫН АРТТЫРЎДА ФИЗИКАЛЫҚ ШЫНЫҒЫЎЛАРДЫҢ ӘҲМИЙЕТИ - Палўанова, Г.Ж.; Қутлымуратов, М.А. (FAN va JAMIYAT, 2016)
The most effective method to develop the endurance of the organism is physical exercises. The article considers information about the benefits of physical exercises for improving the activity of the musculoskeletal system (bones and muscles) and the work of internal organs (digestive, respiratory organs, cardio - vascular system, nervous system, endocrine glands), the development of the endurance of the organism to the negative factors of external and internal environment.